Boosting the anti MERS-CoV activity and oral bioavailability of resveratrol via PEG-stabilized emulsomal nano-carrier: Factorial design, in-vitro and in-vivo assessments. (31st December 2022) - Zakaria, Mohamed Y.; Zaki, Islam; Alhomrani, Majid; Alamri, Abdulhakeem S.; Abdulaziz, Osama; Abourehab, Mohammed A.S.
Abstract: Resveratrol (RSV) is a phytoceutical polyphenolic compound exhibiting a well evidenced wide range of therapeutic activities. Unfortunately, its diminished aqueous solubility and extensive metabolism in gastro intestinal tract (GIT) and liver prohibit its biological activity and systemic availability. Herein the conducted study PEG stabilized emulsomes (PEMLs) were customized to enclose RSV aiming to boost its biological availability and antiviral activity. PEGylating the vesicles not only grant the promoted steric stability of the system but also being beneficial in exaggerating the intestinal permeability and extending the period of circulation of the drug, hence its targeted clinical use. The Investigation of the influence of predetermined variables on the physical characterization of formulae (entrapment efficiency EE%, particle size PS and zeta potential ZP) was implemented utilizing Design Expert® software. (F4) with desirability value (0.772), picked to be the optimal formula, which is fabricated utilizing 35 mg compritol as the lipidic core and 60 mg 1, 2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[amino(polyethylene glycol)-2000] (DSPE-Mpeg-2000). The dominance of the F4 relative to RSV dispersion was affirmed by the data acquired from ex-vivo and pharmacokinetic studies. In addition, F4 exhibited significant lower EC50 value (0.0127 µg/mL) relative to that of RSV dispersion(0.338 µg/mL) by around 26 times denoting the capability of the formulation to boost the antiviral activity. To a great extent, F4 was able to significantly suppress the inflammatory response and oxidative stress resulted from MERS-CoV infection on comparison with RSV dispersion. Finally, the potentiality of PEMLs as nano-panel with boosted both antiviral and oral bioavailability for RSV could be deduced based on the outcomes mentioned herein.